Impact of Trade Liberalization on Wage Skill Premium in Philippine Manufacturing - Rafaelita M. Aldaba (Philippine Institute for Development Studies (PIDS), 2013)
The paper aims to examine how trade liberalization affects wage premium at the firm level. Using effective protection rate as trade proxy, the paper assumes that in the face of increasing competition, an import-substituting firm may decide to remain at the low value-added stage of the production process which requires relatively less skilled workers and suggests a decline in the wage premium. On the other hand, a firm may move away from the product whose protection rate has fallen and shift and expand toward a higher value-added activity. This would require relatively more skilled workers suggesting an increase in the wage premium.The main findings of the paper show that: First, trade liberalization lowers the wage premium. A firm responds to import competition by shifting to the manufacture of products with lower value added and importing intermediate inputs rather than producing these within the plant. Second, using ASEAN tariff rates as trade proxy, the same results are obtained, however, when ASEAN tariff is interacted with skill intensity, the results show that tariff reduction on skill-intensive products is associated with rising wage skill premium. Third, firm characteristics such as skill intensity, firm size, and capital labor ratio matter in assessing the impact of trade reform on the wage premium. Lastly, exports are associated with increasing wage premium at the firm level the higher their skill intensity. In the literature, greater openness is associated with skill-biased technological change with export-oriented and technology-intensive activities as channels.
Keywords: F16; 330; trade liberalization; labor market; Philippines; Philippine manufacturing; wage skill premium